Therapeutic Landscapes in Colorectal Carcinoma - Scanu, Antonio M; De Miglio, Maria Rosaria (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
The Special Issue, titled "Therapeutic Landscapes in Colorectal Carcinoma", illustrates a stimulating collection of articles written by international specialists that can promote discussions and ideas among colleagues working on CRC. It provides us with a deeper insight into the latest advances involving knowledge on CRC from scientific, translational, and clinical points of view. Through this Special Issue, our main purpose was to shed light on some state-of-the-art research on CRC. Here, the reader will find papers on prognostic factors as well as responses to neoadjuvant and adjuvant CRC treatments. Finally, we discuss the research trends and hotspots for CRC therapies that emerged during the COVID-19 pandemic, such as the potential achievement of a transition from CRC clinical research to precision medicine, together with a special emphasis given to new single-cell-based techniques. We hope that it can encourage translational and interdisciplinary collaborations, leading to a definitive understanding of strategies to overcome and inhibit CRC progression and metastasis.